Research progress of psychological nursing in postoperative nursing of patients undergoing percutaneous coronary intervention (心理护理在经皮冠状动脉介入治疗术后护理中的应用进展) - ZENG Qian (曾倩); TANG Yunting (唐云婷) (中西医结合护理)
Patients undergoing percutaneous coronary intervention are vulnerable to develop anxiety and depression. Targeted psychological nursing interventions are required to relieve the negative emotions, improve the drug adherence, reduce the risk of complications and improve the quality of life. This paper reviewed the studies of psychological nursing in postoperative nursing of patients undergoing percutaneous coronary intervention, in order to raise medical worker’s awareness on mental problems of patients and improve the quality of nursing after PCI. (焦虑、抑郁等心理问题是PCI术后患者常见不良情绪, 开展针对性心理护理能有效缓解PCI术后患者负性情绪, 提高患者服药依从性, 降低并发症发生率, 改善生活质量。本文回顾心理护理干预在PCI术后护理中的应用进展, 提高临床医护人员对术后患者心理问题的关注度及护理质量, 从而促进术后康复。)